Evaluation of Islamophobia And Terrorist Risk Perceptions of Tourists Coming to Turkey (Third Sector Social Economic Review, 2025)
Security in tourism is an extremely important issue in order to carry out tourism activities in a healthy manner. Tourists' risk perceptions of any element that threatens their security while engaging in touristic activities or making touristic purchasing decisions have extremely negative consequences for tourism. Following the Twin Tower terrorist attacks on September 11, 2001, the fear of terrorism around the world also resonated with tourists. After this action, as terrorist incidents were associated with Islam, Islamophobic attitudes began to affect tourism activities. The aim of this study is to evaluate the Islamophobia and terrorism risk perceptions of tourists and the behavioral reflections of terrorist activities on tourists and to discuss the perception of security in world tourism on this level. Quantitative research method was adopted in the study; The data was collected using the survey form method. Purposive sampling method was chosen to enrich the study qualitatively. The data obtained was analyzed using quantitative data analysis methods. The findings were interpreted in line with the theoretical framework. As a result of the research, it was concluded that there is a positive relationship between tourists' perception of Islamophobia and terrorism risk.
Keywords: Islamophobia; Terrorism Risk; Tourist; Tourism Safety; Tourism